ANALISIS KELAYAKAN SOSIAL DAN FINANSIAL PEMBUATAN TAMBAK UDANG DI KABUPATEN MUKOMUKO PROPINSI BENGKULU - Wahyuni, Sri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
This research was conducted in Dusun Baru Pelokan Kecamatan Mumomuko Utara Kabupaten Mukomuko from July to September 2007 and aimed analysis feasibility the project of social and financial aspect. The research location was selected purposively. The population in this research was the society of Dusun Baru Pelokan are 415 KK, the sample taken by the Proportional Random Sampling Method. The qualitative analysis used of scor to see perception and people knowledge of Shrimp Culture. The quantitative analysis to show number use investment criteria analysis Gross B/C ratio, Net B/C ratio, Net Present Value, Profitability ratio, Internal Rate of Return (IRR), Payback Periode and Sensitivity Analysis. Key Words : Shrimp Culture, The Feasibility Social and Financial